THE CONTENT ANALYSIS OF HEAVY METALS OF Pb, Cu, Zn, Ni AND ORGANIC MATTER IN THE SEDIMENT OF EAST COAST OF SUMATERA - Fitria, Wahyuni; Amin, Bintal; Samiaji, Joko (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
The research was conducted in August – November 2013. The purpose of this study was to determine the content of heavy metals of Pb, Cu, Zn and Ni in the sediment and its organic matter content in the east coast of Sumatera. The method used was survey method in wich the East coast of Sumatera coastal waters was used as the location of sampling.The results showed that different sediment fraction had different concentration of heavy metals. The sediment fraction of >250 μm had higher concentration than the fraction <63 μm and 63 μm – 250 μm. The concentration of Pb, Cu, Zn and Ni in the sediment were 7.29, 12.91, 8.69 and 14.57 μg/g respectively. Simple linier regression analysis showed of negative corelations for Pb, Cu, and Zn. and positive corelations for Ni with the content of organic matter in the sediment. The Pb, Cu, Zn and Ni concentrations were still below the value of ERL and ERM.Keywords : heavy metals, sediment, organic matter, east coast of Sumatera